Penggunaan Media Gambar untuk Meningkatkan Kemampuan Membaca Permulaan Bahasa Indonesia di Kelas 1B SD Negeri 104202 Desa Bandar Setia - Asmidar Dhalimunthe; Nur Wahyuni (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Early reading ability is a basic skill that is important to be mastered by early grade students as a foundation for learning at a higher level. However, based on observations in class 1B of SD Negeri 104202 Bandar Setia Village, it was found that many students had difficulty in early reading, such as recognizing letters, combining letters into words, and understanding the meaning of simple words. This study aims to improve students' early reading ability through the use of picture media. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. The subjects of this study were 29 students of class 1B of SD Negeri 104202 Bandar Setia Village. This study was conducted at SD Negeri 104202 Bandar Setia Village on Jl. Terusan Dusun V, Bandar Khalifah, Kec. Percut Sei Tuan, Deli Serdang Regency. Data were collected through observation, reading ability test results, and documentation. The results showed that the use of picture media significantly improved students' early reading ability. The improvement is seen from the results of the reading ability test, active student participation during learning, and increased student interest in learning. This can be seen from the results of the assessment carried out starting from the pre-cycle, cycle 1 and cycle 2. The use of visual media to improve Indonesian literacy in elementary schools can improve achievement, ability, and improve student learning outcomes at SD Negeri 104202 Bandar Setia Village. In addition, image media helps students understand the material more easily in a fun and interesting way. The conclusion of this study is that image media is effective as a learning aid to improve early reading skills in early grades. It is hoped that teachers can continue to develop visual-based learning media to create a more interesting and interactive learning atmosphere.